FAKTOR-FAKTOR YANG MEMPENGARUHI POSTPARTUM BLUES - Desfanita ' '; Misrawati ' '; Arneliwati ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Postpartum blues (baby blues)is a sad condition which is faced by certain mothers after giving birth, every mothers has a tendency for having a postpartum blues (baby blues). The purpose of this study is to explore the factors which affect the postpartum blues syndrome. The analysis method of this study used a descriptive correlation design. The study was held in the state hospital of Riau (RSUD Arifin Achmad) and Petala Bumi hospital. A purposive sampling technigue. Was used in this study to choose 75 respondents. The data of the study were collected by using guestionnaires with its validity and reliability have been tested before delivered. Further, the data were analyzed using univariat and bivariat through Chi Square test. The result of the study proves that there is a significant relationship between a husband support and readiness pregnancy with postpartum blues syndrome (p value= (0,000) < α (0,05) and there is no a significant relationship between a kind of childbirth with postpartum blues syndrome (p value= (0,185) < α (0,05). In conclusion, based their knowledge about a husband’s role and support for his wife during pregnancy and after giving birth period. Key words: Baby Blues, Postnatal Reference : 29 (2005 – 2013)